Comparing patient characteristics and treatment processes in patients receiving physical therapy in the United States, Israel and the Netherlands: Cross sectional analyses of data from three clinical databases - Dekker Joost; van den Bosch Wil JH; Deutscher Daniel; Hart Dennis L; Swinkels Ilse CS; de Bakker Dinny H; van den Ende Cornelia HM (BMC, 2008)
Abstract Background Many assume that outcomes from physical therapy research in one country can be generalized to other countries. However, no well designed studies comparing outcomes among countries have been conducted. In this exploratory study, our goal was to compare patient demographics and treatment processes in outpatient physical therapy practice in the United States, Israel and the Netherlands. Methods Cross-sectional data from three different clinical databases were examined. Data were selected for patients aged 18 years and older and started an episode of outpatient therapy between January 1st 2005 and December 31st 2005. Results are based on data from approximately 63,000 patients from the United States, 100,000 from Israel and 12,000 from the Netherlands. Results Age, gender and the body part treated were similar in the three countries. Differences existed in episode duration of the health problem, with more patients with chronic complaints treated in the United States and Israel compared to the Netherlands. In the United States and Israel, physical agents and mechanical modalities were applied more often than in the Netherlands. The mean number of visits per treatment episode, adjusted for age, gender, and episode duration, varied from 8 in Israel to 11 in the United States and the Netherlands. Conclusion The current study showed that clinical databases can be used for comparing patient demographic characteristics and for identifying similarities and differences among countries in physical therapy practice. However, terminology used to describe treatment processes and classify patients was different among databases. More standardisation is required to enable more detailed comparisons. Nevertheless the differences found in number of treatment visits per episode imply that one has to be careful to generalize outcomes from physical therapy research from one country to another.